2016
DOI: 10.1038/gim.2015.125
|View full text |Cite
|
Sign up to set email alerts
|

Multigene panels in prostate cancer risk assessment: a systematic review

Abstract: Prostate cancer is the fourth most common malignancy worldwide, and the second most common among men.1 In 2014, it was estimated that more than a quarter of a million new cases were diagnosed in North America and that the disease accounted for more than 33,000 deaths. 2,3 These numbers are likely to increase with the aging of the population. On the basis of data from the Surveillance, Epidemiology, and End Results program, more men were diagnosed with prostate cancer at a younger age and earlier stage in 2004-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…In particular, there have been concerns on the impact of genetic screening in clinical decision-making. For example, in a previous review, 58 genetic screening was discussed using commercially available SNP panel tests in prostate cancer. Conclusions were that the investigated SNP panels had poor discriminative ability and clinical validity.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there have been concerns on the impact of genetic screening in clinical decision-making. For example, in a previous review, 58 genetic screening was discussed using commercially available SNP panel tests in prostate cancer. Conclusions were that the investigated SNP panels had poor discriminative ability and clinical validity.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer risk prediction by genetic risk scores (GRS) have been designed as an efficient and effective approach in terms of clinical utility [ 9 ]. Recently, genetic risk assessment studies have been reported evaluating the cumulative genetic scores for PCa risk [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modest value of clinicogenomic associations does not mean negligible, and some researchers try to develop polygenic risk models or panels assigning values for various SNP alleles, and calculate the total risk of disease for more effective risk prediction [ 75 ]. In the literature, several cumulative prediction models have been proposed, but most of these are criticized regarding comprehensive evaluation, especially for clinical utility [ 76 ].…”
Section: Resultsmentioning
confidence: 99%